The Authority of the Public Prosecution in UAE Legislation to Conduct Investigations within the Framework of International Judicial Cooperation - Shakir, Humaid; Al-Aani, Mohammad (Journal of Legal Sciences, 2026)
This study aimed to clarify and detail the nature of the powers and jurisdiction of the Public Prosecution Authority in conducting investigative procedures within the framework of international judicial cooperation to combat organized crime. The jurisdiction and authority of the Public Prosecution extend beyond national borders, taking on an international dimension through collaboration with judicial authorities in other countries to confront transnational crimes and ensure that perpetrators do not evade justice for their criminal activities.In this regard, the Public Prosecution exercises its power to investigate perpetrators of organized crime based on its original and inherent jurisdiction throughout all stages of criminal proceedings. These powers are affirmed by national legislation—such as the UAE Criminal Procedure Law and the Law on International Judicial Cooperation in Criminal Matters—as well as international instruments, most notably the United Nations Convention against Transnational Organized Crime.This affirms the Public Prosecution’s capacity to follow up on legal assistance requests related to investigation and inquiry procedures within international cooperation. It further necessitates explicitly confirming the authority of the Public Prosecution to initiate investigative actions linked to international legal assistance, and granting it the exclusive right to receive and assess investigation requests without the involvement of any intermediary judicial authority—thus saving time and effort and enabling prompt action.